Analisis Rasio Aktivitas Sebagai Penilaian Kinerja Keuangan Pada PT. Japfa Comfeed Indonesia Periode 2020-2024 - Monica sari; Gilang Fauzi Rahman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the financial performance of PT Japfa Comfeed Indonesia Tbk, listed on the Indonesia Stock Exchange (IDX), during the period 2020–2024, based on activity ratios. The activity ratio used includes receivable turnover, inventory turnover, and total asset turnover to assess the company’s efficiency in managing assets to support operational activities. The research method used is descriptive with a financial statement analysis approach, using secondary data in the form of annual financial statements obtained from the Indonesia Stock Exchange. The results of the study show that the company’s performance, as measured by the receivable turnover ratio, exceeds industry standards and is categorized as good, indicating the effectiveness of its accounts receivable management. However, performance based on the inventory turnover and total asset turnover ratios is below industry standards. It is categorized as poor, indicating that the company’s inventory management and asset utilization are not optimal. Overall, the analysis shows that although the company has managed receivables well, PT Japfa Comfeed Indonesia Tbk still needs to improve the efficiency of inventory management and asset utilization to enhance operational performance and competitiveness.